Impactos do uso do solo na qualidade da água e comunidade perifítica de sistemas lóticos - Scarlet da Encarnação de Araújo (2022)
The characteristics of an aquatic ecosystem and its water quality are affected by inadequate soil uses. The main types of uses affecting water quality are urban occupation and industrial and agricultural activities, which include effluents release at the water bodies and fertilizers used in the rural areas. The evaluation of only physical and chemical variables may be not sufficient to describe the whole impact of soil uses in the water quality. Thus, the search for bioindicators is necessary, since they can respond to a sum of environmental variables that could explain little about the environment if considered alone. The periphytic community is considered a good bioindicator and an important tool for streams biomonitoring, but it is still little applied in Brazil. Therefore, the goal of this work was to evaluate the capacity of the total periphytic community and also only diatoms to describe the water quality of streams subject to the effects of different soil uses. We analyzed water samples from systems at the hydrographic sub-basin of Rio Ipanema, in Ipatinga (MG), during the rainy and the dry seasons. We collected water and periphyton in six points located in areas that are subjected to different types of soil use and occupation. Two points were located at rural areas, two points at periurban areas and the other two were located at urban areas. Based on chemical analyses, it was observed that the quality of water differed between the sampling points, with Trophic Status Index (IET) varying from ultraoligotrophic to hypereutrophic. The quantification of periphytic community was performed at species level, with data evaluated as total biovolume and diatoms biovolume only. The points of urban areas (Bom Jardim and Foz), more degraded by domestic and industrial sewage, presented larger periphytic biomass. Diatoms were the group of larger biomass and showed higher species diversity, and its quantification allowed to detect bioindicators for impacts at the urban systems, such as Nitzschia palea, Navicula cryptotenella, Gomphonema lagenula, G. parvulum e G. brasiliensis. Thereby, this group of microalgae revealed to be a useful tool to biomonitoring of water quality in the studied environments.